2021
DOI: 10.1186/s12575-021-00158-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Organelles in Rheumatoid Arthritis with Focus on Exosomes

Abstract: Auto-immune diseases involved at least 25% of the population in wealthy countries. Several factors including genetic, epigenetic, and environmental elements are implicated in development of Rheumatoid Arthritis as an autoimmune disease. Autoantibodies cause synovial inflammation and arthritis, if left untreated or being under continual external stimulation, could result in chronic inflammation, joint injury, and disability. T- and B-cells, signaling molecules, proinflammatory mediators, and synovium-specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…Dendritic cells treated with IL-10 have been found to release exosomes and reduce the severity of RA ( 86 ). In addition, dc exosomes treated with IL-10 prevented the invasion of RA in mice and reduced the severity of existing arthritis ( 87 ).…”
Section: Applications Exosomes In Inflammatory Diseasesmentioning
confidence: 99%
“…Dendritic cells treated with IL-10 have been found to release exosomes and reduce the severity of RA ( 86 ). In addition, dc exosomes treated with IL-10 prevented the invasion of RA in mice and reduced the severity of existing arthritis ( 87 ).…”
Section: Applications Exosomes In Inflammatory Diseasesmentioning
confidence: 99%
“…This suppression is done through the regulation of both endogenous T cells and APCs activity, MHC class II-dependent, and an antigen-specific pathway. Exosomes generated from DCs had a similar or even stronger immunosuppressive impact in comparison with their original secreting cells [ 176 , 193 ]. It has been revealed that the indoleamine-pyrrole 2, 3-dioxygenase (IDO) enzyme which degrades tryptophan, has an immunosuppressive capability in a variety of conditions, such as RA.…”
Section: Exosome and Rheumatic Arthritismentioning
confidence: 99%
“…The diverse response to therapy by individual patients may also relate to the tumor microenvironment (TME). Inflammation is a biological process that combines innate and adaptive immune responses with metabolism and various activities that affect cell and organelle integrity and survival ( 7 , 8 ). It has long been recognized that inflammation has a paradoxical effect on tumors ( 9 – 11 ).…”
Section: Introductionmentioning
confidence: 99%